Factors influencing type of contraceptive use among Ghanaian males: Insights from the 2022 Ghana demographic and health survey - Christiana Lokko; Jonathan Sackey; Francis Lokko (Public Health in Practice)
Objectives: This study examines the socio-demographic, media, and health-related factors influencing contraceptive use among men of reproductive age in Ghana. Study design: The 2022 GDHS consists of three datasets which are nationally representative cross-sectional data that elicited the demographic and health indicators of children 0–59 months, women 15–49 years of age, mean aged 15–59 years old as well as households. Methods: This study utilised the 2022 Ghana Demographic and Health Survey (GDHS) men recode file, analysing a sample of 7044 men aged 15–59 years. The dependent variable, contraceptive use, was categorised into modern, traditional, and no method. Data were weighted and cleaned, and multinomial logistic regression was used to identify factors associated with contraceptive use. Results: Among the respondents, 16.6 % used modern contraceptives, 4.3 % used traditional methods, and 79.0 % used no method. Significant predictors of contraceptive use included age, education, ethnicity, region, marital status, wealth index, number of wives/partners, and media exposure (p < 0.05). Men aged 15–54 were more likely to use modern methods, while those with lower education levels were more likely to use no method. Ethnic differences were observed, with Mole-Dagbani men more likely to use modern methods. Media exposure, particularly frequent radio and television consumption, was positively associated with modern contraceptive use. Conclusions: The persistently low uptake of modern contraceptives among men in Ghana hampers efforts to achieve universal access to family planning. Tackling socio-demographic disparities and strengthening media-driven awareness can foster greater male involvement. These findings highlight the need for targeted strategies to enhance male contraceptive use and support shared responsibility in family planning.